Issue of prophylactic removal of lower wisdom teeth – review of guidelines in selected countries - Wojas, Karolina; Zaleska, Małgorzata; Hille, Grzegorz (Journal of Stomatology, 2017)
The presence and eruption of wisdom teeth is often associated with the appearance of various complications in the least expected moment for the patient. On the other hand, however, surgical extraction also is associated with numerous complications. The qualification of patients for the prophylactic removal of the third lower wisdom tooth should be based on evidence. Recently, a lot of scientific research has been done, but there are still many different opinions about this topic. The purpose of this article is to trace the national guidelines defining indications or contraindications for the prophylactic extractions of lower wisdom teeth in selected countries. In order to present the largest cross-section of data, the guidelines of countries from Western Europe, America and Asia have been taken into account. Eight countries were presented, including Poland. Comparing the recommendations from each country there were found numerous discrepancies. In some countries commissions clearly oppose prophylactic extractions, while others have developed appropriate treatment guidelines for specific clinical situations . These algorithms have taken into account age of the patients, the root development stage, the position of the tooth, and the factors related to the patient's life situation.